The schooling system in Matanzas during of the Cuban ten-year war of Independence (1868-1878) - Padrón Ramos, Milagros; Secada Cárdenas, Rosa; Fernández Gutiérrez, Jorge Luis (Atenas, 2017)
One of the main objectives of the subject Cuban History is the knowledge of the local history. It is necessary to define concepts for its approach in the teaching learning process for the professional pedagogical education. The thorough study of the XIX century schooled education in Matanzas and the legacy of its teachers and institutions deeply contribute to this professional development. Nonetheless, it is very important to take into account the different majors for the selection of the topics to be taught. The authors´ main goal is to give arguments of how the people of Matanzas, despite the Spanish repression during the wars of independence, maintained the schooled education.